Spoligotypes of Mycobacterium tuberculosis complex isolates from patients residents of 11 states of Brazil - Gomes, Harrison Magdinier; Elias, Atina Ribeiro; Cardoso Oelemann, Maranibia Aparecida; da Silva Pereira, Marcia Aparecida; Onofre Montes, Fatima Fandinho; Marsico, Ana Grazia; Kritski, Afranio Lineu; dos Anjos Filho, Luciano; Caldas, Paulo C.; Possuelo, Lia Goncalves; Cafrune, Patricia; Rossetti, Maria Lucia; et al. (Elsevier B.V., 2012)
One of the high tuberculosis (TB) incidence countries in the world, Brazil is characterized by considerable differences in TB incidence on regional and state level. In the present study, we describe Brazilian spoligotypes of 1991 Mycobacterium tuberculosis complex (MTC) clinical isolates from patients residents of 11 states from different regions of the country, diagnosed between 1996 and 2005. By performing spoligotyping on a large number of M. tuberculosis clinical isolates, one of the main objectives of this study was to determine the major genotype families causing TB in Brazil and to verify the region-associated genotype distribution. We observed a total of 577 distinct spoligopatterns, 12.6% of these corresponded to orphan patterns while 87.4% belonged to 326 shared-types (SITs). Among the latter, 86 SITs (isolated from 178 patients) had been observed for the first time in this study, the most frequent being SIT2517 which belonged to the T3-ETH lineage and was exclusively found among patients residents of Belem, the capital of the state of Para (n = 8 isolates). Irrespective of shared-type labeling, a total of 19.5% strains were unique (unclustered) in our study as opposed to 80.5% clustered isolates (189 clusters, size range from 2 to 205 isolates). The three largest clusters were SIT42 of the Latin-America & Mediterranean (LAM) 9 clade (10.3%), SIT53 of the T clade (7.6%), and SIT50 of the Haarlem clade (5.4%). The predominant MTC lineages in Brazil in decreasing order belonged to the LAM (46%); the ill-defined T (18.6%); the Haarlem (12.2%), the X (4.7%), the S (1.9%), and the East African Indian (EAI) (0.85%) families. The rest of clades grouped together as Mycobacterium africanum, Mycobacterium bovis, Beijing, Central Asian (CAS), and the Manu types, represented less than 1% of the strains. Finally, about 15% of the isolates showed spoligotype signatures that were not yet classified among well-defined lineages. In conclusion, we provide hereby a first insight into the population structure of MTC isolates in Brazil, showing the predominance of both LAM and T family and the existence of region-associated genotypes. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Mycobacterium tuberculosis; Population structure; Spoligotyping; Brazil; Database